المساجد في إمارة أبوظبي : تاريخها، وتطورها، ودورها : دراسة تحليلية - شامسي، عبد الله سالم عبد الله (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2019)
This study is intended to examine the history of mosques in the Emirate of Abu Dhabi and its role in contributing to the cultural identity of the Emirate. The study is divided into four objectives: First is to study the history of the most important mosques in the Emirate of Abu Dhabi. Second is to explain the stages of the development of mosques in the emirate. Third is to examine the role of the mosque at the present time. Fourth is to identify the most important mosques built and paid for by rulers of the Emirate and parties outside of the UAE and the impact of leadership and culture. The researcher adopted several methods namely the analytical descriptive and a field study as well as comparative study. The analytical descriptive was based on the researcher's references to the history of the most important mosques in the emirate and the ways of building them.The most important results of the study are the existence of a number of historical mosques whose history has never been documented including the mosque that dates back to the Abbasid. Delving into the history of mosques is essential since it is inseparable from the origin of nation that can be traced back as far back to one thousand years ago.